2008
DOI: 10.1016/j.jcp.2007.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Particle simulation of Coulomb collisions: Comparing the methods of Takizuka & Abe and Nanbu

Abstract: The interactions of charged particles in a plasma are in a plasma is governed by the long-range Coulomb collision. We compare two widely used Monte Carlo models for Coulomb collisions. One was developed by Takizuka and Abe in 1977, the other was developed by Nanbu in 1997. We perform deterministic and stochastic error analysis with respect to particle number and time step. The two models produce similar stochastic errors, but Nanbu's model gives smaller time step errors. Error comparisons between these two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 5 publications
2
44
0
1
Order By: Relevance
“…We also find that when a higher-order Milstein correction [11], [12] to the Langevin equations model is included, there is no significant change in the results of the collisional relaxation process for the specific example considered. Results using the binary collision algorithm for the same collisional relaxation test problem have been reported by Wang et al [13]. In the Wang et al study, it was found that the mixing of statistical errors with time-step effects made it difficult to obtain unambiguous and clear scalings of the errors with respect to the time step used.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…We also find that when a higher-order Milstein correction [11], [12] to the Langevin equations model is included, there is no significant change in the results of the collisional relaxation process for the specific example considered. Results using the binary collision algorithm for the same collisional relaxation test problem have been reported by Wang et al [13]. In the Wang et al study, it was found that the mixing of statistical errors with time-step effects made it difficult to obtain unambiguous and clear scalings of the errors with respect to the time step used.…”
Section: Introductionsupporting
confidence: 53%
“…A lack of a clear scaling with time step is also observed for the binary collision algorithm reported in the work of Wang et al [13]. In [13], the binary collison models of [1] and [2] are employed, and convergence with respect to particle number and time step are investigated with the additional feature that ensemble averages are computed over many realizations of the simulations to reduce the statistical variance.…”
Section: Corrections To First-order Euler Integration Of the Grimentioning
confidence: 87%
See 3 more Smart Citations